Study and Design of Online Bookstore Backend - Ding, Yunzheng (Scientific Journal of Technology, 2025)
This article focuses on the actual needs of bookstores and designs and develops a small e-commerce website based on JSP, namely the online bookstore system. The technical solution adopted by the bookstore system is: JSP+Tomcat+SQLServer2000. The main functions of an online bookstore system based on JSP are two-fold: front-end user and back-end management. The main functions of the backend include: adding and deleting book information, querying book information, setting user levels, publishing notifications, managing book categories and publishers, querying and summarizing book sales information, and so on. The system is easy to operate, has stable performance, is easy to maintain and upgrade, and should be supported by a large number of sellers.